Validation of the Second Victim Experience and Support Tool-Revised in the Neonatal Intensive Care Unit. Issue 8 (December 2021) - Winning, Adrien M.; Merandi, Jenna; Rausch, Joseph R.; Liao, Nancy; Hoffman, James M.; Burlison, Jonathan D.; Gerhardt, Cynthia A.
Abstract : Objective: The aim of the study was to validate a revised version of the Second Victim Experience and Support Tool (SVEST-R). The SVEST survey instrument was developed to measure the emotional and professional impact of medical errors and adverse patient events on healthcare providers and can help healthcare organizations evaluate the effectiveness of support resources. Methods: An SVEST-R was completed by 316 healthcare providers from seven neonatal intensive care units affiliated with a large, pediatric hospital. The original 29-item measure was expanded to 43 items to assess eight psychosocial domains (psychological distress, physical distress, colleague support, supervisor support, institutional support, nonwork-related support, professional self-efficacy, resilience) and two employment-related domains (turnover intentions, absenteeism) associated with the second victim experience. Seven additional items assessed desired forms of support (e.g., time away from the unit). A confirmatory factor analysis evaluated the factor structure of the modified measure. Results: The initial confirmatory factor analysis did not reveal an acceptable factor structure; thus, eight items were removed because of inadequate factor loadings or for conceptual reasons. This resulted in an acceptable model for the final 35-item measure. The final version included nine factors (i.e., psychological distress, physical distress, colleague support, supervisor support, institutional support, professional self-efficacy, resilience, turnover intentions, and absenteeism), with Cronbach α ranging from 0.66 to 0.86. Conclusions: The SVEST-R is a valid measure for assessing the impact of errors or adverse events on healthcare providers. Importantly, the SVEST-R now includes positive outcomes (i.e., resilience) that may result from the second victim experience. Abstract : Supplemental digital content is available in the text.